DOI: 10.14264/uql.2016.184
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of speech/language difficulties to health-related quality-of-life in Australian children: a longitudinal analysis

Abstract: Speech and/or language difficulties (SaLD) are among the most frequently observed developmental problems affecting children. Research points to the impact of childhood SaLD on literacy/educational achievement, behaviour and self-esteem; however, there has been limited attention paid to the impact of SaLD, directly or indirectly, on health-related qualityof-life (HRQoL). HRQoL is the impact a particular health condition (or intervention) has on an individual. HRQoL comprises numerous distinct dimensions ('domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 105 publications
1
12
0
Order By: Relevance
“…More detailed analysis of complex risk factor models may provide a better understanding of impacts of social–emotional behaviour, family and environmental factors on the QoL of children with DLD over time (Feeney et al . ). For example, we recommend future studies examine modalities of DLD which are known to vary in response to intervention (e.g., expressive versus receptive) and a more comprehensive set of child, family and environmental factors, including how protective factors, such as family support, home learning environments, and good peer relationships modify impacts of DLD on QoL.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…More detailed analysis of complex risk factor models may provide a better understanding of impacts of social–emotional behaviour, family and environmental factors on the QoL of children with DLD over time (Feeney et al . ). For example, we recommend future studies examine modalities of DLD which are known to vary in response to intervention (e.g., expressive versus receptive) and a more comprehensive set of child, family and environmental factors, including how protective factors, such as family support, home learning environments, and good peer relationships modify impacts of DLD on QoL.…”
Section: Discussionmentioning
confidence: 97%
“…We know that child (e.g., gender, general health), family (e.g., maternal education and mental health), and environmental factors (e.g., socioeconomic status, parents' engagement in work) contribute to both language and social-emotional development (Bayer et al 2012, Reilly et al 2010) and children's QoL when parents have concerns regarding their child's speech and language development (Feeney et al 2017). Children also need adequate language skills to develop their social relationships, to engage with school learning, and to learn how to manage and self-regulate their behaviour , Conti-Ramsden et al 2013).…”
Section: Predicting Qol In Children With Dldmentioning
confidence: 99%
See 1 more Smart Citation
“…Socioeconomic status was determined by the census-derived Socio-Economic Indexes for Areas (SEIFA) disadvantage score based on the family's home postcode (Australian Bureau of Statistics, 2009). These characteristics were specified a priori based on the literature (Feeney et al, 2017;van Agt et al, 2010;Vella et al, 2015) and used as confounders in both the multivariable linear regression and mixed effect models. As we were interested in the association of child HRQoL and LL regardless of aetiology, we did not intend to delineate the effects of LL from cognitive abilities or other comorbidities by including these factors as confounders.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have explored constructs such as well-being and HRQoL in children with DLD and ASD. Feeney, Desha Kahn, and Ziviani (2017) indicated that parental reports of concern about receptive language, for children aged 4–9, were negatively associated with HRQoL across all domains. They suggested that DLD is associated with reduced HRQoL, concluding that typically developing speech and language skills is a protective factor for HRQoL in children.…”
mentioning
confidence: 99%